Listado de especies de escarabajos coprófagos (Coleoptera: Scarabaeidae: Scarabaeinae) de bosque seco de Colombia (2016)
The species list of dung beetles of the dry forest of Colombia from the Entomological Collection of the Alexander von Humboldt Institute is presented. A total of 19.797 specimens of 68 species, the largest number of species registered for different localities in dry forest in Colombia, were reviewed. The taxonomic problems within the subfamily Scarabaeinae in Colombia are discussed; and a unique code for each morpho-species is proposed to further the the standardization of identification for records that cannot be identified to species. Only 35 species (51 %) could be identified to species, the others were codified.